Distributive Struggle and the Self in the Early Modern Iberian World - Cwik, Christian; König, Hans-Joachim; Rinke, Stefan (Historamericana, 2022)
This book examines the nexus between distributional struggle and the fashioning of the self in the context of Iberian globalization. Bringing together scholars of the Spanish and Portuguese empires, it explores how men and women, conversos, creoles, indios, etc. acted in their efforts to influence the ways in wealth and honors were being distributed.